The white princess [videorecording (DVD)] - Comer, Jodie; Benson, Rebecca; Collins-Levy, Jacob (Anchor Bay Entertainment, 2017)
The white princess is a tale of power, family, love and betrayal, charting one of the most tumultuous times in British history uniquely from the point of view of the women. The tempestuous marriage between Elizabeth of York and King Henry VII officially marks of the conclusion of the War of the Roses, but the real battle for the throne is far from over.